Sistem Imbalan Dalam Islam Menemukan Keseimbangan Antara Keadilan Dan Motivasi - Delastri, Yefrineng; Jamilus, Jamilus (Peneliti.net, 2024)
Reward systems are an important component in organizations, both modern organizations and in the Islamic context. In Islam, the reward system should be based on the principles of fairness, transparency and accountability, and aim to motivate individuals to contribute their maximum and achieve common goals. This article discusses reward systems in Islam with a focus on the balance between fairness and motivation. It discusses the basic principles of Islamic reward systems, the different types of reward systems that can be used, and the challenges of implementing a fair and motivating reward system.The article also provides recommendations for designing an effective Islamic reward system, taking into account the context and needs of the organization, as well as the principles of Islamic sharia.A fair and motivating reward system is an important element in Islamic organizations. By applying Islamic principles and following the recommendations mentioned above, organizations can design a reward system that is effective and helps achieve common goals. Translated with DeepL.com (free version)